Characterization and corrosion behavior of graphene oxide-hydroxyapatite composite coating applied by ultrasound-assisted pulse electrodeposition. Issue 16 (November 2017) - Fathyunes, Leila; Khalil-Allafi, Jafar
Abstract: Hydroxyapatite (HA) coating reinforced with graphene oxide (GO) had been developed for getting rid of restrictions associated with its brittleness. This study introduced a promising method of ultrasound-assisted pulse electrodeposition to fabricate the GO-HA coating on the anodized heat-treated surface of titanium. The SEM images indicated that the combined effect of employing ultrasonic waves and GO as a second mechanically resistant phase resulted in the formation of a fine and compact microstructure for the HA-based coating. The EDS elemental maps and micro-Raman spectra showed that the ultrasonic power of 60 W was more effective to incorporate the GO sheets into the coating. However, aggressive agitation of electrolyte with increasing the power to 100 W limited the electrocrystallization of HA crystals in some regions of the surface. The results of nanoindentation test demonstrated the highest nano-hardness (3.08 Gpa) and elastic modulus (41.26 Gpa) for the GO-HA coating prepared by the ultrasound-assisted method. The EDS and FTIR analyses revealed that both the GO sheets and highly reactive OH · radicals produced during the water sonolysis had a positive influence on the mineralization of HA phase. In addition, the pore size distribution diagrams calculated from the N2 adsorption-desorption isotherms indicated a decrease in the pore size of HA crystals for the electro-co-deposited GO-HA sample. Finally, anodizing/heat-treatment process and the incorporation of GO sheets into the coating led to a significant improvement in the corrosion protection of titanium.